2020
DOI: 10.1080/23322039.2020.1799908
|View full text |Cite
|
Sign up to set email alerts
|

Oil price shocks against stock return of oil- and gas-related firms in the economic depression: A new evidence from a copula approach

Abstract: This research examines the influence of world crude oil price shocks on the financial performance of Vietnamese oil-and gas-related firms. Based on copula approach and the sample data of domestic giant oil-and gas firms from 2009 to 2019, in particular in the situation of oil price steadily going up and economic depression of 2011-2012; approximately nine copulas including Gauss, Clayton, Rotated-Clayton, Plackett, Frank, Gumbel, Rotated-Gumbel, Student, Symmetrized-Joe-Clayton have been focused. A new evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Multi-collinearity could exist if the correlation coefficient among variables is 0.8 and more. It means that a strong correlation can be present due to a high value of pairwise collections between independent variables [15,16]. Table 6 shows that the maximum correlation coefficient is 0.7476 and does not exceed 0.8; therefore, we conclude that there is less multi-collinearity in this study.…”
Section: Panel Unit Root Tests (Purts)mentioning
confidence: 54%
See 1 more Smart Citation
“…Multi-collinearity could exist if the correlation coefficient among variables is 0.8 and more. It means that a strong correlation can be present due to a high value of pairwise collections between independent variables [15,16]. Table 6 shows that the maximum correlation coefficient is 0.7476 and does not exceed 0.8; therefore, we conclude that there is less multi-collinearity in this study.…”
Section: Panel Unit Root Tests (Purts)mentioning
confidence: 54%
“…In most cases, fossil fuels are known as the most affected factor that can affect renewables [3,12,13]. Further, fossil fuels have negative and significant impacts in terms of environmental degradation [14][15][16]. In the trends of the fourth industrial revolution and digital transformation, a clean energy and eco-friendly environment are highly sought after.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vietnam has been under pressure to improve its social, economic and legal systems. In competitive environment, the rapid technological change impact on their cost structures, processes and controls and due to recent economic crisis affecting businesses worldwide lead to a decline in performance of organisational so manufacturer need to revise their strategy, manufacuting process and accounting techniques to be able to compete with their rivals (Aji & Husin, 2020;Ismail & Isa, 2011;Le et al, 2020;Nguyen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A new evidence could be found that the oil price shocks have not impacted on the stock return of oil-and gas-related firms in the wave of increasing oil price, but a lagged period of time oil-and gas-related firms could receive more stock returns [12].…”
Section: Introductory Commentmentioning
confidence: 99%